Primary healthcare workers’ COVID-19 infection status following implementation of adjusted epidemic prevention and control strategies: a cross-sectional study in Jiangsu, China - Lu, Beier; Ma, Rongji; Xu, Jinshui; Zhang, Yongjie; Guo, Haijian; Chen, Hualing; Miao, Pengcheng; Qian, Yongkang; Xu, Biyun; Shen, Ya; Chen, Bingwei (Frontiers in Public Health, 2023)
Introduction In times of epidemic outbreaks, healthcare workers (HCWs) emerge as a particularly vulnerable group. This cross-sectional study endeavors to assess the COVID-19 infection rate among the primary HCWs in Jiangsu Province subsequent to the implementation of adjusted epidemic prevention and control strategies. Methods From January 17 to February 2, 2023, an extensive survey was conducted among primary HCWs in Jiangsu Province, employing a self-designed questionnaire. Logistic regression analysis was utilized to identify the factors associated with COVID-19 infection. Results The overall infection rate among primary HCWs stood at 81.05%, with a 95% confidence interval (CI) of 80.61–81.48%. Among those afflicted, cough, fatigue, and fever emerged as the three most prevalent symptoms, each with an incidence rate exceeding 80%. In the context of multivariate logistic regression, an elevated risk of COVID-19 infection was observed in correlation with female gender (adjusted odds ratio [aOR] = 1.12, 95% CI: 1.04–1.21), possessing a bachelor’s degree or higher (aOR = 1.32, 95% CI: 1.23–1.41), accumulating over 10 years of work experience (aOR = 1.28, 95% CI: 1.11–1.47), holding a middle-level cadre position (aOR = 1.22, 95% CI: 1.11–1.35), assuming the role of a unit leader (aOR = 1.30, 95% CI: 1.11–1.54), and working in a fever clinic for 1 to 10 days per month (aOR = 1.42, 95% CI: 1.29–1.57). Conversely, advanced age (aOR = 0.76, 95% CI: 0.70–0.82), being underweight (aOR = 0.78, 95% CI: 0.69–0.90), current smoking (aOR = 0.64, 95% CI: 0.57–0.71), receiving 4 doses of COVID-19 vaccine (aOR = 0.49, 95% CI: 0.37–0.66), and pregnancy or perinatal status (aOR = 0.85, 95% CI: 0.72–0.99) were associated with a diminished risk of infection. Conclusion Following the implementation of adjusted policies, a substantial proportion of primary HCWs in Jiangsu province contracted COVID-19. Female gender and younger age emerged as risk factors for COVID-19 infection, while no discernible link was established between professions and COVID-19 susceptibility. The receipt of COVID-19 vaccines demonstrated efficacy in curtailing the infection rate, underscoring the significance of bolstering prevention knowledge and heightening self-protective awareness among primary HCWs.